ปัจจัยการพัฒนาการท่องเที่ยวเชิงสร้างสรรค์ในเส้นทางวัฒนธรรม กรณีศึกษา : ชุมชนท่องเที่ยวเชิงวัฒนธรรมย่านเมืองเก่าริมแม่น้ำเพชรบุรี - จันทร์วงศ์ ศรัญญู (วารสารศิลปกรรมศาสตร์วิชาการ วิจัย และงานสร้างสรรค์, 2022)
Study the factors of local tourism in the old city cultural tourism community along the Phetchaburi River that can be useful for the development of creative tourism in the community. It focuses on studying the cultural capital of the community, including the participation and support potential of community tourism that can contribute to the benefit of the development factors of creative tourism in the community. Which the study method by reviewing the literature and analyzing the documents together with quantitative and qualitative data collection The results of the study found that 1) Cultural capital of there, it’s at a high level. When considering each aspect, every aspect was at a high level, consistent with in-depth interviews. 2) Participation of there, it was at a low level, but from the opinions of the interviewees, the community’s participation was at a high level because the sample group had different variables from the interviewee group. And tourism potential to accommodate tourists of there, it is at a high level in all aspects. 3) Be able to consider the factors causing the development of creative tourism components in community which consists of factors in four aspects: management factors access factor Participation factor and attraction factor.